Thrive the plant-based whole foods way to staying healthy for life - Brazier, Brendan (Da Capo Lifelong, 2017)
Discusses the long-term health benefits of a plant-based diet and outlines a twelve-week meal plan that combines 150 allergen-free recipes with raw food options to help achieve optimal health and boost energy.